Estimasi Sumberdaya Batubara Pada Pit Timur, PT. Allied Indo Coal Jaya, Kota Sawahlunto, Sumatera Barat - Muhammad Faiz; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2022)
PT. Allied Indo Coal Jaya conducts mining using open pit mining and underground mining methods. With coal prices relatively rising, the company plans to expand mining area in Eastern Pit. The references in the pit expansion plan and strategic mining plan is to estimate and model resources. The estimation of resources at PT Allied Indo Coal Jaya uses a comparison of the Geostatistics method (OrdinaryaKriging) with the Conventional (Polygon) method. Which Geostatistics method is more favored because it considers spatiality. Ordinary Kriging tends to produce block estimates that are more evenly distributed or less varied than the actual levels. The methode Polygon is a conventional method and is commonly applied to deposits that are relatively homogeneous and have a simple geometry. From the results of estimating and modeling coal resources in the Pit Timur of PT Allied Indo Coal Jaya, the OrdinaryaKriging method provides total coal resource of 5,678,887.5atons and the Polygon method provides total coal resource of 6,537,342atons. Meanwhile, in the comparison of resource models from the two methods with original situation using correlation analysis, the value of the coefficient of determination in the Ordinary Kriging method was obtained more large compared to Polygon method.